How does the belt and road initiative affect the carbon emissions of China’s cities? - Zhang, Junxia; Li, Pingyan; Liza, Farzana Fatima; Ahmad, Fayyaz; Lv, Cuixi; Cao, Zijian (Frontiers in Environmental Science, 2023)
There is growing concern about carbon emissions as the economy grows, which is of great importance to the implementation of the green Belt and Road Initiative(BRI) development strategy. Using panel data of 282 prefecture-level cities in China from 2006-2020 and the difference-in-difference method, this paper empirically examines the effects of the BRI on carbon emissions. Both theoretical and empirical analyses indicate that the BRI can significantly reduce the carbon emission level of cities along the route, but the impact varies in different regions and cities. The mechanism analysis shows that the BRI reduces the carbon emission level of cities along the Belt and Road through the economic agglomeration effect and industrial structure effect. Therefore, China should vigorously promote green Belt and Road construction, implement a regional integration strategy, and promote the transformation and upgrading of the industrial structure. These findings have a certain reference value for the follow-up implementation of the BRI.